Sensing Eco-Ethical Concerns in Boyle’s A Friend of the Earth - Mainali Sharma , Chintamani (Bon Voyage, 2025)
Climate change is one of the most crucial and sensitive issue of the present age. It has been challenging the human civilization with a red siren, jeopardizing not only the survival of human beings but also on the entire flora and faunas on the planet. Meanwhile, extreme anthropocentricism and the ignorance of ethical consumerism have been gearing up the situation more catastrophic. This article examines and analyses ecological disaster depicted in T C Boyle’s A Friend of the Earth (2000) by employing a key tenet of ecocriticism. It further focuses on the interplay between anthropocentric agencies, ecological catastrophe and human emotional responses of ecocide. Drawing Greg Garrard’s ecocritical framework and Aldo Leopold’s “Land Ethics” this paper excavates how Boyle’s narrative prophesizes visceral sense of dystopia. Boyle illustrates the creepy imageries of nature to trace the pathetic and tragic situations of his characters, especially Tyrone Ty Tierwater (Ty), who is reduced to the last stage of his survival. With the infusion of eco-ethical values, he (Ty) along with other characters keeps struggling to conserve remaining rare animals from being extinct and to save the ecosystem, despite his old and weak age. Consequently, this article exposes the Boyle’s prophesy of dystopian future resulted by deterioration of natural ecology, under-toned in the narrative.